Percevoir et transformer la frontière. L’œuvre de Günter Grass comme processus de borderscaping - Dorothée Cailleux (Recherches Germaniques)
This article aims to study the work of Günter Grass in the light of the concept of ‘borderscaping’. After briefly evoking the origin of the concept and the related theoretical background, we show how Grass’s work questions the notion of frontier in various ways. First, the aim is to show that, particularly in the Danzig trilogy, Günter Grass attempts to describe a geographical area in which languages, traditions and cultures are mixed, regardless of the physical German-Polish borderline. A second part devoted to Unkenrufe analyzes how the author denounces the creation of hermetic immaterial borders, at the very moment when the new geographical boundaries seem to promise the end of the confrontation between nations. A final part of this paper attempts to show how the history of the reception of Grass’s work in Poland fully illustrates the process of deconstruction of the frontier that literature is able to achieve, because it can influence the representations of readers on the border and create a new mental landscape.